Determinants of patient satisfaction in health center services in Indonesia - Harahap, Preti Sinta; Siregar, Putra Apriadi; Gurning, Fitriani Pramita (Science Midwifery, 2025)
Patient satisfaction is a crucial indicator in assessing the quality of health services in Community Health Centers (Puskesmas). As the primary healthcare providers at the community level in Indonesia, Puskesmas play a vital role in ensuring accessible, affordable, and comprehensive health services. High patient satisfaction not only reflects the effectiveness of healthcare delivery but also influences patient adherence to medical recommendations, trust in the healthcare system, and overall public health outcomes. Therefore, understanding the factors that determine patient satisfaction is essential for improving service quality and formulating effective healthcare policies. Quality health services in Community Health Centers are one of the main indicators in increasing patient satisfaction. This study aims to analyze the determinants of patient satisfaction with Community Health Center services in Indonesia using secondary data from the 2017 Health Manpower Research (Risnakes). The research design uses a quantitative approach with Spearman Rank correlation analysis to see the relationship between independent variables, such as speed of service, friendly attitude of officers, communication, patient rights, and quality of health service facilities, to the dependent variable, namely patient satisfaction. The results showed that speed of service had the most dominant influence on patient satisfaction (r = 0.792; p < 0.05), followed by quality of service facilities (r = 0.473; p < 0.05) and the right to choose health services (r = 0.283; p < 0.05). Other factors, such as friendliness of officers, communication, and confidentiality of patient information, showed a weak but significant relationship. Overall, the independent variables contributed 99% to the dependent variable. This study emphasizes the importance of improving the efficiency of services and physical facilities in Community Health Centers to improve patient satisfaction. These findings are expected to be a reference in formulating better health service policies in Indonesia.